Impact of Anterior Commissure Involvement and Frozen Guided Resections on Oncological Outcomes after Laser Cordectomy in Early Glottic Cancers – A 10-year Retrospective Analysis from a Tertiary Care Cancer Center in India - Elizabeth Mathew Iype; Ankit Vishwani; Bipin T Varghese; Shaji Thomas; Sahya S Lal (Journal of Head & Neck Physicians and Surgeons)
Background: Early glottic cancers can be treated using different options such as transoral laser microsurgery (TLM), open partial laryngectomy (OPL), and radiation therapy (RT). TLM provides similar oncological benefits to OPL in a few subsets of patients, and the quality of voice is comparable to RT, while hospitalization time is reduced. Resection by laser microsurgery of early glottic cancer with anterior commissure involvement (ACI) is more challenging mainly due to difficulty in adequate exposure. The frozen section is reliable in TLM for determining the extent of resection and the real depth which may be masked on videoscopy. Materials and Methods: This study is a retrospective analysis of patients with early glottic cancer (Tis, T1) who underwent TLM in a tertiary cancer center in South India from January 1, 2012, to December 31, 2019. All patients were identified from the hospital registry. Results: The study included 89 patients, and the median follow-up was 54 months. Out of 89 patients, 14 patients had local recurrence which was managed with salvage TLM/salvage RT/salvage laryngectomy. There were three patients with nondisease-specific deaths. Among the study population, the laryngeal preservation rate was 96.6%, the cause-specific survival rate was 100%, and the overall survival rate was 97.7%. The 3-year disease-free survival rate was 84.4%. ACI and frozen margin positivity were statistically significant poor prognostic factors. Conclusion: TLM is a safe and effective treatment of early glottic carcinoma. Apart from tumor (T) staging, ACI and frozen positivity were negative predictive factors. The results suggest the need to consider ACI in the T staging of glottic tumors. Frozen positivity helps us in re-excision but signifies that the disease is deeply infiltrative or aggressive and a vigilant follow-up is required for these patients.